Hysteresis and thermodynamic properties of water sorption in ‘Malagueta’ pepper seeds - Silva, Hellismar W. Da; Rodovalho, Renato S.; Silva, Isneider L. (Departamento de Engenharia Agrícola - UFCG, 2018)
The objective of this study was to determine hysteresis, enthalpy, entropy, enthalpy-entropy compensation theory and Gibbs free energy for water adsorption and desorption in ‘Malagueta’ pepper seeds. Hygroscopic equilibrium moisture contents were determined by the static gravimetric method, with water activity in the range from 0.29 to 0.90 and temperatures of 30, 40 and 50 °C. The hysteresis of the ‘Malagueta’ pepper seeds reduces with the increase of temperature. Enthalpy, entropy and Gibbs free energy of adsorption and desorption increase with the reduction of the moisture content of the seeds. The enthalpy-entropy compensation theory is valid for the sorption processes. The sorption of water between seeds and the surrounding air is a non-spontaneous process.

Objetivou-se, neste trabalho, determinar histerese, entalpia, entropia, teoria da compensação entalpia-entropia e a energia livre de Gibbs para os processos de adsorção e dessorção de água em sementes de pimenta malagueta. Os teores de água de equilíbrio higroscópico foram determinados pelo método estático gravimétrico, com atividade de água na faixa de 0,29 a 0,90 e temperaturas de 30, 40 e 50 °C. A histerese das sementes de pimenta malagueta reduz com o aumento da temperatura. A entalpia, entropia e energia livre de Gibbs de adsorção e dessorção aumentam com a redução do teor de água das sementes. A teoria da compensação entalpia-entropia é válida para os processos sortivos. A sorção da água entre as sementes e o ar envolvente é um processo não espontâneo.
Histerese e propriedades termodinâmicas de sorção de água em sementes de pimenta malagueta
Keywords: Capsicum frutescens L.; enthalpy; entropy; Gibbs free energy; Capsicum frutescens L.; entalpia; entropia; energia livre de Gibbs